2020
DOI: 10.1159/000510556
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Effect of Net Ultrafiltration Rate among Critically Ill Adults Receiving Continuous Renal Replacement Therapy

Abstract: <b><i>Introduction:</i></b> In continuous renal replacement therapy (CRRT)-treated patients, a net ultrafiltration (NUF) rate &#x3e;1.75 mL/kg/h has been associated with increased mortality. However, there may be heterogeneity of effect of NUF rate on mortality, according to patient characteristics. <b><i>Methods:</i></b> To investigate the presence and impact of heterogeneity of effect, we performed a secondary analysis of the “Randomized Evaluation of Norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Slow UF with fluid removal rate of 1–1.75 mL/kg/h has been proposed to be an optimal target [728]. This allows for progressive removal of the fluid from the serum that is matched to plasma refill rate, hence leading to gradual unloading of fluid from the interstitium that can be tolerated by a patient with tenuous hemodynamic status.…”
Section: Discussionmentioning
confidence: 99%
“…Slow UF with fluid removal rate of 1–1.75 mL/kg/h has been proposed to be an optimal target [728]. This allows for progressive removal of the fluid from the serum that is matched to plasma refill rate, hence leading to gradual unloading of fluid from the interstitium that can be tolerated by a patient with tenuous hemodynamic status.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, given the diminished fluid tolerance intrinsic to COVID-AKI, the process of fluid removal mandates an individualized approach, congruent with each patient's unique fluid tolerance [ 118 ]. Just as in resuscitation, the adoption of a functional hemodynamic algorithm during fluid removal could be superior to a generic approach [ 119 , 120 , 121 , 122 , 123 , 124 , 125 ]. This tailored strategy aims to prevent both under-resuscitation scenarios, characterized by residual vascular and extravascular congestion, and over-resuscitation scenarios, which may result in low cardiac output and hypotension (see Table 5 ).…”
Section: Treatmentmentioning
confidence: 99%
“…The investigators concluded that UF NET >1.75 ml/kg per hour was independently associated with increased hospital mortality, and this effect was not mediated by fluid balance, low BP, vasopressor use, hypokalemia, or hypophosphatemia (18). In another study, the investigators evaluated the heterogeneity of effect of UF NET in critically ill patients receiving CKRT and found that both high and low UF NET rates may be harmful, especially in those with edema, sepsis, and greater acuity of illness severity (19). When evaluating kidney recovery, one study found that UF NET >1.75 ml/kg per hour was independently associated with lower kidney recovery rates (20).…”
Section: Effect Of Ufnet On Mortalitymentioning
confidence: 99%